2020
DOI: 10.7554/elife.54940
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channels implement a molecular leaky integrator that detects action potentials and regulates neuronal firing

Abstract: Voltage-gated sodium channels play a critical role in cellular excitability, amplifying small membrane depolarizations into action potentials. Interactions with auxiliary subunits and other factors modify the intrinsic kinetic mechanism to result in new molecular and cellular functionality. We show here that sodium channels can implement a molecular leaky integrator, where the input signal is the membrane potential and the output is the occupancy of a long-term inactivated state. Through this mechanism, sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 84 publications
8
52
0
1
Order By: Relevance
“…An analysis of Nav current in dorsal raphe neurons supports a similar dual-pathway model (Milescu et al, 2010), although the molecular basis for the inactivation in dorsal raphe neurons has not been determined. An accumulation of Nav channels in slow recovery states in raphe neurons has been proposed to act as a molecular integrator that essentially reports AP frequency and regulates firing (Navarro et al, 2020). A strength of the results presented here is that the rat CC currents are likely to arise from a single category of Nav channel, localized exclusively on the spherical plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of Nav current in dorsal raphe neurons supports a similar dual-pathway model (Milescu et al, 2010), although the molecular basis for the inactivation in dorsal raphe neurons has not been determined. An accumulation of Nav channels in slow recovery states in raphe neurons has been proposed to act as a molecular integrator that essentially reports AP frequency and regulates firing (Navarro et al, 2020). A strength of the results presented here is that the rat CC currents are likely to arise from a single category of Nav channel, localized exclusively on the spherical plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…An important pair of papers on Nav currents in dorsal raphe neurons (Milescu et al, 2010; Navarro et al, 2020), almost certainly involving some as yet unidentified FGF, provides some of the more useful comparative information to the results presented here. Interesting differences between the Nav currents in CCs and those in dorsal raphe are that, whereas in CCs, inactivated channels are about equally distributed between fast and slow recovery pathways during a single depolarizing step, in dorsal raphe neurons only about 20% of channels enter initially slow recovery pathways (Milescu et al, 2010; Navarro et al, 2020). At present, we lack sufficient quantitative information about the differential entry and rates of recovery among different cell types to draw any conclusions, but below we consider a few factors that will need to be considered in future work.…”
Section: Discussionmentioning
confidence: 87%
“…Long-term Nav inactivation described in other systems (Dover et al, 2010; Navarro et al, 2020) has been shown or proposed to involve inactivation mediated by intracellular fibroblast growth factor homologous factors (abbreviated either FGFs or FHFs) (Smallwood et al, 1996; Munoz-Sanjuan et al, 2000). This family of proteins consists of a family of four peptides (FGF11-FGF14, also known as FHF3, FHF1, FHF2, or FHF4, respectively) with splice variation at the N-terminus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations